Elevated serum complement levels and higher gene copy number of complement C4B are associated with hypertension and effective response to statin therapy in childhood-onset systemic lupus erythematosus (SLE) - Evan Mulvihill; Stacy Ardoin; Susan D Thompson; Bi Zhou; Gakit Richard Yu; Emily King; Nora Singer; D M Levy; Hermine Brunner; Yee Ling Wu; Haikady N Nagaraja; Laura Eve Schanberg; et al. (Lupus Science and Medicine)
Objective Systemic lupus erythematosus (SLE) features high frequency of cardiovascular disease (CVD) and fluctuating complement levels. The clinical trial Atherosclerosis Prevention in Pediatric Lupus Erythematosus (APPLE) aimed to evaluate whether atorvastatin treatment reduced the progression of atherosclerosis in 221 patients with childhood-onset SLE (cSLE), using carotid intima media thickness (CIMT) as surrogates. We leveraged APPLE biorepository and trial data to investigate the relationship between complement and CVD in cSLE.Methods Gene copy numbers (GCNs) for total C4, C4A and C4B were measured by TaqMan-based real-time PCR and Southern blotting, and analysed with laboratory and clinical parameters through Student’s t-test and χ2 analyses. Effects of total C4, C4A and C4B GCNs on the response to placebo or atorvastatin treatment and progression of CIMT were examined by regression analyses.Results At baseline, C4 protein levels strongly correlated with GCNs of total C4 (p=1.8×10−6). Each copy of C4 gene increased mean serum C4 by 3.28 mg/dL. Compared with those without hypertension (N=142), individuals with hypertension demonstrated significantly elevated serum levels for C4 and C3 at baseline and serially (C4: P=5.0×10−25; C3: P=5.84×10−20). Individuals with ≥2 C4B genes had 2.5 times the odds of having hypertension (p=0.016) and higher diastolic blood pressure (p=0.015) compared with those with C4B deficiency. At the study end, subjects with ≥2 C4B and atorvastatin treatment had significantly slower increase in CIMT compared with those treated with placebo (p=0.018).Conclusions cSLE with hypertension had elevated serum levels of C4 and C3 and higher GCN of C4B; cSLE with ≥2 C4B genes would benefit from statins therapy to prevent atherosclerosis.